Marketing Management Strategies in Increasing New Student Enrollment - Dheista Galin Anggraini; Ade Akhmad Saputra (Cipta Pustaka Nusantara, 2025)
The current development of technology and the internet at SD Negeri 01 has a significant impact on the marketing sector. People are now increasingly familiar with various social media, such as Facebook, Instagram, Line, and Telegram. In addition to functioning as a communication tool, social media has also become one of the most effective means of promotion. This study aims to analyze the role of social media in promoting programs in elementary schools. The method used is qualitative with a descriptive approach, where data sources are obtained through interviews, observations and interviews. Data analysis techniques using data reduction, and conclusion drawing. The results of the field research revealed that social media plays a very crucial role in supporting the success of program marketing at the primary school level. Social media acts as a bridge between the school and the community, allowing information to be shared quickly and efficiently. In addition, primary schools also utilize social media platforms to convey information about various activities, such as available facilities, competitions and other activities. The use of social media in promoting schools has reached an optimal level and contributed significantly to the increase in new learner enrollment. However, schools still need to innovate and be creative in developing their promotional strategies through social media.